Perencanaan Disposal Semi Induced Flow dan Finger Flow di PT Vale Indonesia Tbk, Kabupaten Luwu Timur, Provinsi Sulawesi Selatan - Rizki Amalia; Dzul Fajrin; Aryanti Virtanti Anas; Hasliana Alimuddin (Jurnal Penelitian Enjiniring, 2019)
Disposal Planning of Semi Induced Flow and Finger Flow in PT Vale Indonesia Tbk, East Luwu Regency, South Sulawesi Province). PT Vale Indonesia Tbk produces sizable nickel ore, which is an average of 75,000 tons per year and the overburden is around four times the amount of nickel ore production, thus requiring good disposal planning.Disposal planning includes disposal design, allocation of the number of dozers, disposal life length, and disposal costs. The research locations are Watulabu 16C DP and Watulabu 19 DP in West Block Area and Nickel Hill 15 DP and Nayoko 01 DP in East Block Area. Watulabu 16C DP and Nickel Hill 15 DP are semi-induced disposal, while Watulabu 19 DP and Nayoko 01 DP are disposal finger flow. Each disposal has two units dozer. The dozers used are dozer D8R Caterpillar. Disposal planning was made using Maptek Vulcan and Microsoft Excel software. Based on the results of the research, the disposal design of Watulabu 16C DP has a surface area of ​​72,229.40 m2 and a volume of 125,959.92 m3, Nickel Hill 15 DP has a surface area of ​​92,375.68 m2 and a volume of 128,344.04 m3, Watulabu 19 DP has a surface area of ​​129,061.97 m2 and volume of 775,396.21 m3, and Nayoko 01 DP has a surface area of ​​227,318.16 m2 and volume of 1,270,176.94 m3. The disposal life length of Watulabu 16C DP is 1.5 weeks (11 days), Nickel Hill 15 DP is 1.4 weeks (10 days), Watulabu 19 DP is 7.5 weeks (53 days), and Nayoko 01 DP is 11.2 weeks (79 days). The disposal cost of Watulabu 16C DP is $51,841.49, Nickel Hill 15 DP is $138,061.15, Watulabu 19 DP is $370,924.26, and Nayoko 01 DP is $957,625.14.